ACCEPTANCE RATE OF EMERGING TECHNOLOGIES IN AGRITOURISM FROM GORJ - Elena Loredana STĂNCIOIU (Fiabilitate şi Durabilitate)
This study investigates the acceptance rates of emerging technologies within the agritourism sector in Gorj. Agritourism, a burgeoning niche in the tourism industry, offers visitors immersive experiences in rural settings, often intertwined with traditional agricultural practices. The integration of emerging technologies such as mobile applications, virtual reality, and IoT (Internet of Things) devices holds promise for enhancing visitor engagement, operational efficiency, and sustainable practices in agritourism establishments. However, the extent to which these technologies are embraced by agritourism operators and visitors remains underexplored, particularly in the context of Gorj. This research aims to fill this gap by examining the factors influencing the adoption of emerging technologies in agritourism ventures and assessing their impact on visitor experiences and business outcomes.